Multi-Scale Imaging of Vascular Pathologies in Cardiovascular Disease - Tiwari, Ashish; Elgrably, Betsalel; Saar, Galit; Vandoorne, Katrien (Frontiers in Medicine, 2022)
Cardiovascular disease entails systemic changes in the vasculature. The endothelial cells lining the blood vessels are crucial in the pathogenesis of cardiovascular disease. Healthy endothelial cells direct the blood flow to tissues as vasodilators and act as the systemic interface between the blood and tissues, supplying nutrients for vital organs, and regulating the smooth traffic of leukocytes into tissues. In cardiovascular diseases, when inflammation is sensed, endothelial cells adjust to the local or systemic inflammatory state. As the inflamed vasculature adjusts, changes in the endothelial cells lead to endothelial dysfunction, altered blood flow and permeability, expression of adhesion molecules, vessel wall inflammation, thrombosis, angiogenic processes, and extracellular matrix production at the endothelial cell level. Preclinical multi-scale imaging of these endothelial changes using optical, acoustic, nuclear, MRI, and multimodal techniques has progressed, due to technical advances and enhanced biological understanding on the interaction between immune and endothelial cells. While this review highlights biological processes that are related to changes in the cardiac vasculature during cardiovascular diseases, it also summarizes state-of-the-art vascular imaging techniques. The advantages and disadvantages of the different imaging techniques are highlighted, as well as their principles, methodologies, and preclinical and clinical applications with potential future directions. These multi-scale approaches of vascular imaging carry great potential to further expand our understanding of basic vascular biology, to enable early diagnosis of vascular changes and to provide sensitive diagnostic imaging techniques in the management of cardiovascular disease.